ETNOBOTANI POHON DI DESA BUKIT BATU PADA AREAL HTI PT. BHATARA ALAM LESTARI KECAMATAN SUNGAI KUNYIT KABUPATEN MEMPAWAH - Jamilah, Nurul; Herawatiningsih, Ratna; Kartikawati, Siti Masitoh (JURNAL HUTAN LESTARI, 2019)
This research aims to study the utilization and processing of tree species in daily activities by the community of Bukit Batu Village. Respondents is select using snowball sampling method, field observations and study literature. The results of the study are 22  types of tress from 15 family that  been used by the socsiety of Bukit Batu village, Sungai Kunyit Subdistrict, Mempawah Regency. Of these 22 tree spescies divided into 4 groups including building 10 species, firewood 5 species, boat 7 species, and medicine1 species.  The most widely used part of the tree is the stem 95%, twigs and branches 22%, and the  laest used is the skin part which is as much as 4% by the people of Bukit Batu Village.Keywords: Bukit Batu Village,  ethnobotany, useful plants, snowball sampling